Discharge of lithium-ion batteries in salt solutions for safer storage, transport, and resource recovery. Issue 4 (April 2022) - Torabian, Mohammad Mahdi; Jafari, Milad; Bazargan, Alireza
The use of lithium-ion batteries (LIBs) has grown in recent years, making them a promising source of secondary raw materials due to their rich composition of valuable materials, such as Cobalt and Nickel. Recycling LIBs can help reduce fossil energy consumption, CO2 emissions, environmental pollution, and consumption of valuable materials with limited supplies. On the other hand, the hazards associated with spent LIBs recycling are mainly due to fires and explosions caused by unwanted short-circuiting. The high voltage and reactive components of end-of-life LIBs pose safety hazards during mechanical processing and crushing stages, as well as during storage and transportation. Electrochemical discharge using salt solutions is a simple, quick, and inexpensive way to eliminate such hazards. In this paper, three different salts (NaCl, Na2 S, and MgSO4 ) from 12% to 20% concentration are investigated as possible candidates. The effectiveness of discharge was shown to be a function of molarity rather than ionic strength of the solution. Experiments also showed that the use of ultrasonic waves can dramatically improve the discharge process and reduce the required time more than 10-fold. This means that the drainage time was reduced from nearly 1 day to under 100 minutes. Finally, a practical setup in which the tips of the batteries are directly immersed inside the salt solution is proposed. This creative configuration can fully discharge the batteries in less than 5 minutes. Due to the fast discharge rates in this configuration, sedimentation and corrosion are also almost entirely avoided.